Perinatal programming : the state of the art - Plagemann, Andreas (De Gruyter, 2012)
Perinatal Programming addresses the environment-dependent setting of fundamental life functions and dispositions for diseases in developmental periods during pregnancy and in early infancy. It provides a new view of the origins of health and diseases. To realize these associations may enable us to prevent diseases for the long term. This book reviews actual state-of-the-art knowledge in the perinatal programming field. The authors are internationally known scientists of this research area.